2017
DOI: 10.1007/s11661-017-4278-4
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Texture Evolutions of Biomedical Ti-13Nb-13Zr Alloy Processed by Hydrostatic Extrusion

Abstract: A biomedical b-type Ti-13Nb-13Zr (TNZ) (wt pct) ternary alloy was subjected to severe plastic deformation by means of hydrostatic extrusion (HE) at room temperature without intermediate annealing. Its effect on microstructure, mechanical properties, phase transformations, and texture was investigated by light and electron microscopy, mechanical tests (Vickers microhardness and tensile tests), and XRD analysis. Microstructural investigations by light microscope and transmission electron microscope showed that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The X-ray diffractograms of the tested specimens are depicted in Figure 7. In each of them, peaks can be observed that can be attributed to the Ti13Zr13Nb substrate ( Figure 7) [42]. For the sample with the TiO2 nanotubular layer, the difference in relative intensities of the primary phases (support) of peaks at the 2θ range of 35-42° may have been linked to the formation of the layer visible in the SEM and AFM micrographs (Figures 1 and 3, respectively).…”
Section: Structure and Morphology Of Composite Tio2-chitosan-nanosilvmentioning
confidence: 95%
“…The X-ray diffractograms of the tested specimens are depicted in Figure 7. In each of them, peaks can be observed that can be attributed to the Ti13Zr13Nb substrate ( Figure 7) [42]. For the sample with the TiO2 nanotubular layer, the difference in relative intensities of the primary phases (support) of peaks at the 2θ range of 35-42° may have been linked to the formation of the layer visible in the SEM and AFM micrographs (Figures 1 and 3, respectively).…”
Section: Structure and Morphology Of Composite Tio2-chitosan-nanosilvmentioning
confidence: 95%
“…BIOMATERIAL candidates for long-lasting dental implantology must demonstrate a combination of low elastic modulus, [1][2][3][4] biocompatibility, [5][6][7] and corrosion resistance [8][9][10] when exposed to the various organic and inorganic substances present in the human body. Meeting these requirements are Ti-based materials that lack potentially toxic elements such as commercially pure a Ti (CP-Ti) [11,12] and metastable b Ti alloys with ultra-low elastic modulus that are currently under development.…”
Section: Introductionmentioning
confidence: 99%
“…This structure has the ability to transform at 883 °C to a BCC (body-centered cubic) crystal structure, referred to as the β phase. In the case of the Ti-13Nb-13Zr alloy, its β-stabiliser is the niobium, which affects the microstructure and phase composition resulting in stability of the β phase at a lower temperature [ 44 ]. Microscopic images obtained by scanning electron microscopy indicate the presence of the acicular phase α with martensitic origin (transformed β) in the β phase matrix ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%